Case Report: Evaluating toxic encephalopathy from occupational 1,2-dichloroethane exposure: magnetic resonance imaging contributions - Jieru Wang; Jieru Wang; Tianzi Jian; Guangcai Yu; Guangcai Yu; Baotian Kan; Baotian Kan; Wei Li; Xiangdong Jian (Frontiers in Toxicology)
Background1,2-Dichloroethane is a commonly used industrial solvent. Acute or subacute occupational exposure can cause toxic encephalopathy; however, long-term changes in brain imaging are not frequently documented.Case presentationA 39-year-old woman developed dizziness and forgetfulness 9 days after performing glue coating. Her symptoms improved significantly after a 7-day break from work. However, after resuming work for 3 days, she returned with dizziness, headache, and anxiety. Brain magnetic resonance imaging (MRI) showed extensive edema and diffuse abnormal signal intensities in the cerebellar dentate nucleus, basal ganglia, and bilateral cerebral white matter. She was treated with salvianolate injection, magnesium isoglycyrrhizinate, and neurotrophic therapy. Two weeks after admission, her symptoms improved significantly, except for mild uncoordinated walking. The range of abnormal MRI signals remained consistent with previous findings. She was discharged the following day. She experienced worsened headache 3 days later. Computed tomography revealed diffuse cerebral edema. Despite treatment with mannitol, her headache rapidly worsened and was accompanied by nausea, vomiting, hypertension, bradycardia, and dyspnea, ultimately leading to unconsciousness. Follow-up MRI showed findings similar to the previous scan, except that the apparent diffusion coefficient (ADC) sequence had changed from hypointense to hyperintense. Shortly after the MRI examination, she experienced respiratory arrest. Unfortunately, she died 32 days after her initial admission due to severe cerebral injury and infection.ConclusionOccupational exposure to 1,2-dichloroethane can lead to toxic encephalopathy, presenting as diffuse progressive cerebral edema. This case shows that brain imaging findings may not always correlate with the patient’s clinical condition, so careful monitoring is essential.